ASSESS THE APOPTOTIC EFFECT OF CRUDE EXTRACT OF ROOT POWDER OF WITHANIA SOMNIFERA IN BREAST CANCER CELL LINE - Anni1; Munawar Fazal2* (Chelonian Research Foundation, 2024)
Background: Cancer is one of the greatest health challenges in the developing countries. About half (51%) of cancers occurred in developing countries in 1975. In 2018, this proportion was 55% in 2018 and will projected to reach 61% in 2050. Notably, breast cancer alone contributes to 30% of female cancer cases. It was evident that bioactive component (withaferin –A) of root of Withania somnifera has capacity to work against the breast cancer. In this present study, the crude methanolic extract of root of Withania somnifera screened for in vitro apoptotic activity on MCF-7 and MDA-MB-231 cell line. In Ayurveda, Withania somnifera is commonly known as Ashwagandha, its roots are specifically used in medicinal and clinical applications. It possesses numerous therapeutic actions which include anti-inflammatory, anticancer, sedative, hypnotic and narcotic. Objectives: To Assess the apoptotic activity of crude extract of root of Withania somnifera on breast cancer cell line. Materials and Methods: MDA-MB-231 and MCF-7 breast cancer cell lines, DMEM complete media, 10% fetal bovine serum (FBS), MEM nonessential amino acids, gentamicin and 10μg/mL insulin. MCF-7 and MDA-MB-231 cells were treated with different concentration of sample (crude extract of root powder of Withania somnifera for 24 hrs incubation. Cytotoxicity was measured by MTT assay. The morphological change of untreated (Control) and treated cells were observed under digital inverted microscope and photographed. Results: The lower concentration of sample show less cytotoxic activity on both cell line MCF-7 and MDA-MB-231. Higher concentration of sample show more cytotoxic activity on both cell line MCF-7 and MDA-MB-231.The IC50 value of crude extract of root powder of Withania somnifera against both MCF-7 and MDA-MB-231 was determined. Conclusions: The crude methanolic extract of root of Withania somnifera have anticancer potential but additional studies required. Keywords: Apoptosis, Withania somnifer, cancer, MCF-7, MDA-MB-231, withaferin A.